Ebola and the airplane – securing mobility through regime interactions and legal adaptation. (23rd November 2018) - Cuinn, Gearóid Ó; Switzer, Stephanie
Abstract: This article concentrates on a particular controversy during the 2014 Ebola outbreak in West Africa; the mass cancellation of flights to and from affected countries. This occurred despite authoritative advice against such restrictions from the World Health Organization (WHO). During a public health emergency such as Ebola, the airplane sits at a site of regulatory uncertainty as it falls within the scope of two specialist and overlapping domains of international law; the WHO International Health Regulations (2005) and the Convention on International Civil Aviation. We explore how legal technicalities and objects, by promoting functional interactions between these two specialized regimes of law, were utilized to deal with this uncertainty. We show how the form and function of these mundane tools had a significant impact; assimilating aviation further into the system of global health security as well as instrumentalizing the aircraft as a tool of disease surveillance. This encounter of regimes was law creating, resulting in new international protocols and standards designed to enable the resumption of flights in and out of countries affected by outbreaks. This article therefore offers significant and original insights into the hidden work performed by legal techniques and tools in dealing with regime overlap. Our findings contribute to the wider international law literature on fragmentation and enrich our understanding of the significance of relational regime interactions in international law.